FPGA Implementation of A∗ Algorithm for Real-Time Path Planning - Yuzhi Zhou; Xi Jin; Tianqi Wang (International Journal of Reconfigurable Computing)
The traditional A∗ algorithm is time-consuming due to a large number of iteration operations to calculate the evaluation function and sort the OPEN list. To achieve real-time path-planning performance, a hardware accelerator’s architecture called A∗ accelerator has been designed and implemented in field programmable gate array (FPGA). The specially designed 8-port cache and OPEN list array are introduced to tackle the calculation bottleneck. The system-on-a-chip (SOC) design is implemented in Xilinx Kintex-7 FPGA to evaluate A∗ accelerator. Experiments show that the hardware accelerator achieves 37–75 times performance enhancement relative to software implementation. It is suitable for real-time path-planning applications.